Comparative analysis of softwares for assessment and prediction of radiation situation indicators - Kruk, Yulianna E.; Mostovenko, Andrey L.; Nilova, Ekaterina C.; Kuzminchuk, Viktor A.; Voitenko, Kirill Yu. (Journal of the Belarusian State University. Ecology, 2021)
This article presents the results of comparative analysis of software tools for assessing and predicting parameters characterizing the radiation situation in the event of a hypothetical emergency at nuclear facilities. To analyze the output parameters and rank the software according to the degree of conservatism, an emergency scenario at the AES-2006 design facility was selected. This scenario is associated with a decrease in the coolant temperature and, as a consequence, a change in reactivity. The results of ranking software tools for use in the activities of the Information and Analytical Center of the Department of Nuclear and Radiation Safety are presented. It has been established that the highest degree of conservatism is embedded in the operational assessment codes (HotSpot and RECASS Express). These tools make it possible to provide quick simplified calculations for the early stage of an accident at a Nuclear Facility and can be recommended for use in assessing and predicting the radiation situation as the first tools. In this case, the status of the assessment of the radiation situation is recommended to be considered preliminary, additional to the main calculations performed, for example, with the JRODOS and RECASS NT design codes, the technical capabilities of which allow assessing the radiation impact, including at significant distances from the source, as in the case of emergency situations, and within the framework of the command and staff exercises.
Keywords: software tools; emergency situations; radiation situation; beyond design basis accidents; volumetric activity; pollution density